Financial valuation of Las Vegas Sands Corp - Gomes, Sérgio (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Intersectoral Linkages in Booming Sector Economies - Gomes, Sérgio Ricardo Santos; Marques, Joao Alexandre Lobo; Reis, Ricardo Ferreira (ICEME 2022: 2022 13th International Conference on E-business, Management and Economics, 2022)

The Probability Flow in the Stock Market and Spontaneous Symmetry Breaking in Quantum Finance - Arraut, Ivan; Lobo Marques, João Alexandre; Gomes, Sergio (Mathematics, 2021)
The spontaneous symmetry breaking phenomena applied to Quantum Finance considers that the martingale state in the stock market corresponds to a ground (vacuum) state if we express the financial equations in the Hamiltonian form. The original analysis for this phenomena completely ignores the kinetic terms in the neighborhood of the minimal of the potential terms. This is correct in most of the cases. However, when we deal with the martingale condition, it comes out that the kinetic terms can also behave as potential terms and then reproduce a shift on the effective location of the vacuum (martingale). In this paper, we analyze the effective symmetry breaking patterns and the connected vacuum degeneracy for these special circumstances. Within the same scenario, we analyze the connection between the flow of information and the multiplicity of martingale states, providing in this way powerful tools for analyzing the dynamic of the stock markets.
Keywords: Hermiticity; conservation of the information; degenerate vacuum; flow of information; martingale condition; random fluctuations; spontaneous symmetry breaking; vacuum condition